A rare acute abdomen cause: intestinal perforation and invagination secondary to malignant melanoma metastasis: Intestinal perforation due to malignant melanoma - Dinçer, Onur İlkay and Dincer, Aydın and Koşar, Mehmet Nuri (Journal of Surgery and Medicine, 2022)
Malignant melanoma (MM) is a tumor with high metastatic potential. The small intestine is the third most common metastasis area for MM. Intestinal obstruction, intussusception, hemorrhage, and perforation have been determined as the clinical presentation in patients who were admitted to the hospital because of abdominal pain, weakness, constipation, weight loss, and palpable abdominal mass. Presentation as perforation is rarer than the other clinical presentations. We report the case of a patient with metastatic MM, who attended the emergency department because of acute abdomen. Perforation and invagination due to metastatic lesions were cured by surgical intervention. Possible metastasis should be considered in patients with active complaints or in patients scheduled for emergency intervention, as in our case, if there is a history of MM. Possible metastasis should be considered in preoperative planning, information, and anticipation of the operative procedure.